Investigation of the reaction mechanism of the hydrolysis of MgH2 in CoCl2 solutions under various kinetic conditions - Coskuner Filiz, Bilge (SPRINGER, 2021)
This paper reports kinetic investigation on dehydrogenation kinetics of magnesium hydride (MgH2) in aqueous solutions of cobalt chloride (CoCl2) under various conditions. For this aim, various CoCl2 solutions (2.5-10 wt%) as activator and hydrolysis temperatures (293-363 K) were tested for achieving active hydrogen production by breaking out passive surface. nucleation-growth and surface area approaches were used for investigation of dehydrogenation mechanism and samples characteristic features were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The optimum activator concentration was determined as 6.25 wt% CoCl2 with fastest hydrogen production rate 18.55 mL min(-1) g(-1) with complete conversion of MgH2 to Mg(OH)(2) at room temperature. The kinetic and thermodynamic assessments of dehydrogenation were deduced basing on power law kinetic models with Arrhenius and Eyring approaches. Experimental results dedicated that this approach provided practical and basic application for hydrogen generation by using macroscale MgH2 particles in presence of CoCl2 solution via inhibiting formation of passivation layer with 20 kJmol(-1) apparent activation energy. [GRAPHICS] .
Keywords: Magnesium hydride; Hydrogen; Kinetic; Corrosive; Cobalt chloride; HYDROGEN GENERATION; PERFORMANCE; CHLORIDE; METAL; NANOPARTICLES; COMPOSITE; SYSTEM; COBALT; NI; Chemistry